Effect of solids on gas-liquid mass transfer - Costa, J. (2009)
The effect of the solids on the mass transfer characteristics in a bubble column was studied experimentally for the systems air/water/Polyvinyl chloride (PVC) and air/water/glass beads. Volumetric liquid side mass transfer coefficient, kLa, was determined under different solid concentrations, gas flow rates and solid sizes. The presence of solids affects negatively kLa being this effect more pronounced for the largest particles. For smaller size particles, surface properties play an important role in mass transfer as opposite effects in kLa are observed for the hydrophobic and hydrophilic particles.